2022
DOI: 10.1124/molpharm.121.000354
|View full text |Cite
|
Sign up to set email alerts
|

Senolytic-Mediated Elimination of Head and Neck Tumor Cells Induced Into Senescence by Cisplatin

Abstract: Therapeutic outcomes achieved in head and neck squamous cell carcinoma (HNSCC) patients by concurrent cisplatin-based chemoradiotherapy initially reflect both tumor regression and tumor stasis. However, local, and distant metastasis and disease relapse are common in HNSCC patients.In the current work, we demonstrate that cisplatin treatment induces senescence in both p53 wildtype HN30 and p53 mutant HN12 head and neck cancer models. We also show that tumor cells can escape from senescence both in vitro and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 88 publications
1
15
0
Order By: Relevance
“…We and others have demonstrated that the senolytic ABT-263 (navitoclax), is effective at the elimination of tumor cells induced into senescence by various chemotherapeutic strategies in breast, lung, head and neck and prostate tumor cells ( 14 16 ). However, one fundamental limitation in the use of ABT-263 is thrombocytopenia, given that the target of ABT-263 is the Bcl-xL protein, upon which platelets depend for survival ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…We and others have demonstrated that the senolytic ABT-263 (navitoclax), is effective at the elimination of tumor cells induced into senescence by various chemotherapeutic strategies in breast, lung, head and neck and prostate tumor cells ( 14 16 ). However, one fundamental limitation in the use of ABT-263 is thrombocytopenia, given that the target of ABT-263 is the Bcl-xL protein, upon which platelets depend for survival ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Andrew Yeudall (Augusta University, GA). Cells were cultured in DMEM (Thermo Fisher Scientific, MA) supplemented with 10% (v/v) fetal bovine serum (GeminiBio, CA), 100 U/ml penicillin G sodium and 100 µg/ml streptomycin sulfate (Thermo Fisher Scientific, MA) at the 37°C incubator with 5% CO 2 (Ahmadinejad et al, 2022).…”
Section: Cell Culture and Drug Treatmentmentioning
confidence: 99%
“…Clonogenic survival assay was performed as previously described (Ahmadinejad et al, 2022;Xie et al, 2022). Cells were seeded at a low density (1 x 10 2 HN12 in 6-well plates or 5 x 10 2 HN30 in 10 cm dishes), and exposed to 5 µM cisplatin in the absence and presence of 1 µM PF-04457845.…”
Section: Toxicity Of Cisplatin and Faah Inhibition On Cancer Cells By...mentioning
confidence: 99%
“…For example, H1299 non-small cell lung cancer cells exposed to camptothecin can regain proliferative ability upon discontinuation of drug exposure, although recovery from the senescent growth arrest was a rare event (approximately, 1 in 10 6 cells) [ 69 ]. Our own laboratory has also previously demonstrated that several tumor cell types (specifically, H460 lung, HCT116 colon, HN30 head and neck, Myc-CaP prostate, and 4T1 breast cancer cells) induced into senescence by exposure to chemotherapy or ionizing radiation can overcome the senescent growth arrest following short-term drug or radiation treatment [ 70 , 71 , 72 ].…”
Section: Oncogene-induced Senescencementioning
confidence: 99%